Effect of Mucuna pruriens leaves in dairy cow feed on gas production, digestibility and rumen fermentation by using in vitro gas production technique - Yeanpet, C.; Pilajun, R.; Lunpha, A.; Glinubon, J. (International Journal of Agricultural Technology, 2022)
The results showed that the Mucuna pruriens leaves at 10% in feed affect dry matter and organic matter digestibility which higher than with the control group (p<0.05). However, M. pruriens leaves in all level were not different among dietary treatments on the gas production from the immediately soluble fraction, the gas production from the insoluble fraction, and the gas production rate constant for the insoluble fractionand the potential extent of gas productio. Therefore, it can use M. pruriens leaves at 10% in dairy cow feed.